2022
DOI: 10.1038/s41598-022-26773-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characteristics and stability analysis of surrounding rock reinforcement in rectangular roadway

Abstract: The stability of surrounding rock with bolt support depends on the stability within the reinforcement range. To understand the reinforcing mechanism of a rectangular roadway bolt fully and accurately, a quantitative method for evaluating the stability of the surrounding rock of a rectangular roadway must be developed. First, a roof beam model of a rectangular tunnel is established according to the deformation law of surrounding rock. Based on the elastic–plastic theory, the deflection calculation formula can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Many scholars have carried out fuzzy research on the 'reinforcement force' or 'anchorage stress' generated in the reinforcement of anchor bolts, but relatively few studies have evaluated the scope of bolt action [18][19][20] . Based on the roof failure of a soft rock roadway in the 150202 working face of the Youzhong Coal Mine as the research background, this paper analyses and summarizes the causes of failure.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have carried out fuzzy research on the 'reinforcement force' or 'anchorage stress' generated in the reinforcement of anchor bolts, but relatively few studies have evaluated the scope of bolt action [18][19][20] . Based on the roof failure of a soft rock roadway in the 150202 working face of the Youzhong Coal Mine as the research background, this paper analyses and summarizes the causes of failure.…”
Section: Introductionmentioning
confidence: 99%
“…On-site monitoring demonstrated that the outcomes complied with engineering specifications and might serve as a guide for mines with comparable geology. In the numerical study of the reinforcement effect of rock bolts on enhancing the stability of the surrounding rock, Gu et al [22] concluded that rock bolts can effectively improve the stability of surrounding rock. At the Yuandian no.…”
Section: Introductionmentioning
confidence: 99%